Jaminan Perlindungan yang Berkeadilan bagi Tenaga Kerja Difabel Akibat Kecelakaan Kerja - Ayu Dian Pratiwi; Pius Triwahyudi (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2019)
This research aims to determine the suitability of the protection provided by business actors to workers with disabilities due to workplace accidents with Law No. 13 of 2003 concerning labor and other regulations relating to the protection of disabled workers. This study is a normative legal research that is prescriptive with statute approach and conseptual approach. Legal materials used include primary and secondary legal materials. The data collection techniques used are library studies, Cyber media, and field studies to directly clarify with BPJS Ketenagakerjaan Surakarta and PT. PLN Surakarta. The results of the study showed that the protection of disabled workers due to workplace accidents at PT. PLN Surakarta has not been fully implemented equitably. The companies in Surakarta have been cooperative enough to implement statutory provisions that prohibit the dismissal of workers for being disabled or sick due to workplace accidents, but this company has no special training and facilities provided to disabled workers, and in terms of employee recruitment also requires prospective employees to have complete physical conditions. In fact, with the different physical conditions (disabilities) after workplace accidents, the company should provide special training and facilities to support the physical shortcomings of workers as a form of responsibility. The law such as Constitution of 1945, Law Number 13 of 2003 concerning Labor and other related regulations are sufficiently complete in regulating the protection of rights for disabled workers, but in its implementation have not been fully implemented by business actorsKeywords: Equitable Protection, Disabled Workers, Workplace Accident.